Pupil participation in the development of school culture - Merja Tiusanen (University of Aberdeen, School of Education, 2017)
In Finland, the recognition of children's rights to agency and voice in the educational process has a long-standing tradition. These rights are further underscored in the process of developing the new national core curriculum for Finnish preschool and basic education. The latest school curriculums in Finland emphasize students' participation as well as the development of school cultures. Democracy, equality and human rights also belong to the core of the Finnish educational system, and they are essential in citizenship education (Finnish National Board of Education 2014). Children's involvement and possibility to influence matters related to themselves promotes the child's growth into an active citizen and gives preparedness to act in the democratic and equal society of the future. School has a big influence on the wellbeing of primary school aged children as an influential development environment. Discussion related to school is often only between the adults. How do the young themselves see their possibilities of participating and how do the participatory mechanisms that currently exist in schools meet their individual desires? Within the context of democracy in educational practices, the objective of this on-going research project is to find out in what way are involvement and equality practiced in the school culture. This paper is written from an empirical point of view. On the basis of the research material concerning children's involvement as well as its analysis, it will be possible to develop the concept of an involvement culture of children in a goal-oriented way, equally emphasizing the point of view of everyone - including the quiet children.